Unique characteristics of the tumor immune microenvironment in young patients with metastatic colorectal cancer - Griffith, Brian D.; Lazarus, Jenny; McGue, Jake; Krishnan, Santhoshi; D’Angelica, Michael I.; Shia, Jinru; Dobrosotskaya, Irina; Shi, Jaiqi; Edwards, Jacob; Rao, Arvind; Frankel, Timothy L. (Frontiers in Immunology, 2023)
Metastatic colorectal cancer (mCRC) remains a common and highly morbid disease, with a recent increase in incidence in patients younger than 50 years. There is an acute need to better understand differences in tumor biology, molecular characteristics, and other agerelated differences in the tumor microenvironment (TME). 111 patients undergoing curative-intent resection of colorectal liver metastases were stratified by age into those <50 years or >65 years old, and tumors were subjected to multiplex fluorescent immunohistochemistry (mfIHC). There was no difference in infiltration or proportion of immune cells based upon age, but the younger cohort had a higher proportion of programmed death-ligand 1 (PD-L1) + expressing antigen presenting cells (APCs) and demonstrated decreased intercellular distance and increased cellular engagement between tumor cells (TCs) and cytotoxic T lymphocytes (CTLs), and between TCs and APCs. These trends were independent of microsatellite instability in tumors. These findings suggest a more active immune microenvironment in younger patients with colon cancer.